Winning Customer through Green Marketing: Examining How and When Green Marketing Affects Green Purchase Intention - Muhammad Sharaiz; Raheel Farooqi; Kaenat Malik PhD; Sana Azher; Syed Rizwan Ali (Al-Qanṭara, 2025)
The current study was conducted to empirically investigate the effect of green prices, green products, green places and green promotion on the green brand image along with the role of green brand image in the determination of customer buying intention. The study also considered the moderating effect of social class between green brand image and customer buying intention. The current study selected the quantitative investigative work approach with a selection of explanatory research type. The study also opted cross-sectional design with the application of a survey method for the data gathering and the use of a questionnaire as a tool for data gathering. The targeted population of the current study focused people of Karachi city to understand the perception of green marketing practices among them and its effect on green brand image and green buying intention. The study took a sample size of 384 and followed convenience sampling for response gathering. The collected data is executed with the structural equation model using Smart PLS. The results of the study revealed that there is a considerable effect of green price, place, product and promotion on the green brand image with the significance values of 0.0352, 0.0010, 0.0141 and 0.0000 accordingly. Furthermore, the coefficient values reported for the green price, place, product and promotion on the green brand image are 0.1567, 0.2307, 0.1427 and 0.3314 accordingly. This shows the positive determination of green brand image from green marketing mix with the considerable effect of green brand image on the green buying intention with a coefficient value of 0.6677 along with a significance value of 0.000. However, the moderating effect of social class has not found considerable in between green brand image and green buying intention.